2018
DOI: 10.18203/2320-6012.ijrms20180318
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of platelet count in severe preeclampsia, mild preeclampsia and normal pregnancy

Abstract: Background: Preeclampsia, the most common of hypertensive disorders of pregnancy is an idiopathic multisystem disorder affecting 2 – 10% of all pregnancies and together they form one member of the deadly triad, along with hemorrhage and infection that contribute greatly to the maternal morbidity and mortality rates. The identification of this clinical entity and effective management play a significant role in the outcome of pregnancy. Platelet count is emphasized to play a significant role in hemostasis mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
6
7
2
Order By: Relevance
“…A study conducted in Asia [ 49 ] came to the same conclusion. A study conducted in Korea found a statistically significant positive association between PDW and MAP, while other PLT indices did not demonstrate a significant correlation, contrary to our findings [ 29 ]. However, another investigation identified MPV as a pre-eclampsia severity marker [ 51 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A study conducted in Asia [ 49 ] came to the same conclusion. A study conducted in Korea found a statistically significant positive association between PDW and MAP, while other PLT indices did not demonstrate a significant correlation, contrary to our findings [ 29 ]. However, another investigation identified MPV as a pre-eclampsia severity marker [ 51 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Analysis of platelet counts according to gestational period revealed a significant decrease of platelets from 24 weeks onwards in PE group compared to normotensive group (Table 4). Similar results in PE women about platelet counts were obtained by Gupta A et al, Al Sheeha et al, Gupta A et al, Annam V et al, in their studies [2][3][4][5] We also, observed a significant thrombocytopenia in severe pre-eclampsia women compared to those with mild (Table 5), which was in corroboration with studies by Gupta A et al, Gupta A et al, Somya et al [2,4,6]. However, Ceyhan and coworkers, found no significant difference between the platelet count in pre-eclamptic and normotensive pregnant control women [7].…”
Section: Discussionsupporting
confidence: 87%
“… 25 , 26 Although patients in both groups were age-matched in between 20-40 years, but even in this range we found older age females in the preeclampsia group ( p <0.02) as compared to the control group which shows that elder age is a risk factor for preeclampsia. Similar results were shown by Dong et al 16 However, Gupta et al, 27 and Priyadarshini et al, 28 observed no significant differences between the mean gestational age of patients and controls. This discordance may be because the latter study only included subjects having gestational ages higher than 20 weeks.…”
Section: Discussionsupporting
confidence: 84%